Probiotic Properties of Lactococcus lactis Strains Isolated from Natural Whey Starter Cultures - Ida De Chiara; Rosangela Marasco; Milena Della Gala; Alessandra Fusco; Giovanna Donnarumma; Lidia Muscariello (Foods, 2024)
Lactococcus lactis is a lactic acid bacterium (LAB), generally recognized as safe, and has been widely used in the food industry, especially in fermented dairy products. Numerous studies have evaluated the technological and probiotic properties of lactococci; however, few studies have reported the probiotic characteristics of L. lactis strains isolated from dairy products. In this work, probiotic potential, including survival in simulated gastric juice, tolerance to bile salts, hydrophobicity, and auto- and co-aggregation, was evaluated in L. lactis strains from natural whey starter cultures. The results highlighted the potential probiotic properties of some strains under study, which showed high values of hydrophobicity and auto-aggregation and low values of co-aggregation with the tested pathogenic strains. In addition, studies of safety parameters, such as antibiotic susceptibility and haemolytic activity, confirmed the safety status of all strains under study. Finally, the four most promising strains were investigated for their ability to inhibit the enteroinvasive Escherichia coli (EIEC) and Salmonella Typhimurium adhesion to epithelial cells, using a model of co-cultured epithelial cells. The results demonstrated that L. lactis strains A3-A5-I4-I7 showed the ability to compete with pathogens as well as the ability to exert a protective effect on cells previously infected with E. coli or S. Typhimurium. The identification of new probiotic LAB strains from dairy products aims to produce novel functional foods.